Hexahedral mesh smoothing via local element regularization and global mesh optimization. (February 2015) - Wei, Peng; Lu, Detang; Huang, Tao; Wang, Lei
Abstract: The quality of finite element meshes is one of the key factors that affect the accuracy and reliability of finite element analysis results. In order to improve the quality of hexahedral meshes, we present a novel hexahedral mesh smoothing algorithm which combines a local regularization for each hexahedral mesh, using dual element based geometric transformation, with a global optimization operator for all hexahedral meshes. The global optimization operator is composed of three main terms, including the volumetric Laplacian operator of hexahedral meshes and the geometric constraints of surface meshes which keep the volumetric details and the surface details, and another is the transformed node displacements condition which maintains the regularity of all elements. The global optimization operator is formulated as a quadratic optimization problem, which is easily solved by solving a sparse linear system. Several experimental results are presented to demonstrate that our method obtains higher quality results than other state-of-the-art approaches. Graphical abstract: Highlights: A novel local to global hexahedral mesh smoothing algorithm is proposed. An element size adjustment method is proposed to scale transformed ideal elements. The volumetric Laplacian operator is used to stitch the regularized elements. Geometric constraints of surface meshes are introduced to global optimization.